Análise da variabilidade intrapopulacional entre duas cepas de Ancylostoma ceylanicum utilizando marcadores mitocondriais - João Alexsander Silva Costa (2023)
The indiscriminate use of benzimidazoles for the treatment of hookworm may select strains resistant to treatment. Single nucleotide polymorphisms (SNPs) in codons 167, 198 and 200 of the gene encoding β-tubulin isotype 1, the drug's target protein, are associated with resistance to benzimidazoles in nematodes. In previous work by our research group, a strain of Ancylostoma. ceylanicum resistant to albendazole was isolated by selective pressure from the drug from a wild strain of A. ceylanicum maintained for more than 15 years in an experimental model. The objective of this work was to analyze the intrapopulation molecular variability of the albendazole-resistant strain in comparison with the wild-type strain, as well as to evaluate the percentage of presence of SNPs previously identified after four years of strain selection. Amplifications of the COI gene, NAD1 and codons 198 and 200 of the gene encoding β-tubulin isotype 1 of the two strains of wild-type A. ceylanicum and resistant to albendazole treatment were carried out using conventional PCRs followed by sequencing. No SNPs were found in codons 198 and 200 of the resistant strain and, to exclude strain exchange, samples of the wild-type strain were also sequenced. Samples of the wild strain, as expected, did not present the mutations, proving that there was a reversal of the strain's resistance character. Analyzes for mitochondrial markers demonstrated a low nucleotide diversity, of 0.16% for the COI gene, and 0.25% for the NAD1 gene. When building phylogenetic trees based on two methods, the Maximum Likelihood method and Bayesian Inference, very similar patterns were observed when comparing the two models for both markers, with high bootstrap values, reinforcing the topology of the phylogenetic trees. This result was not at all surprising, considering that the original strain had been without the possibility of recombination with other populations for many years. The low genetic diversity found in both molecular markers, COI and NAD1 and the absence of SNPs in the isotype 1 β-tubulin gene suggests that the combination of the bottleneck effect, genetic drift and the absence of gene flow were, together, responsible due to the low genetic variability of the population. The data presented here contribute to the advancement of knowledge on population genetics of hookworms, in addition to serving as a basis for developing future control strategies and developing new pharmacological therapies.